Model Pendampingan Bisnis Kecil Berbasis Kearifan Lokal Dalam Meningkatkan Pendapatan Masyarakat: Penelitian - Dewi Maharani; Muhammad Fatkhurohman Albashori; Yeni; Purwaka Hari Prihanto; Yovita Yulia M. Zai (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the model of local wisdom-based small business mentoring in increasing community income. This study uses a descriptive qualitative approach. The subjects in this study were small business owners, mentors, traditional leaders, and village officials. The informant selection technique used purposive sampling. Data collection techniques in this study were in-depth interviews, participatory observation, and documentation. Data analysis techniques used were data reduction, data presentation, and conclusion drawing and verification. Then, data validity was tested using source and method triangulation, as well as member checking. The results of this study are that the local wisdom-based small business mentoring model is not only an alternative approach, but also a strategic solution in building an inclusive and sustainable people's economy. By implementing strategies such as mapping local potential, strengthening social capital, contextual knowledge transfer, and product innovation based on local culture can increase community income, as well as strengthen cultural identity, social solidarity, and community independence.